2021
DOI: 10.1093/molbev/msab050
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Purifying and Background Selection on the Inference of Population History: Problems and Prospects

Abstract: Current procedures for inferring population history generally assume complete neutrality - that is, they neglect both direct selection and the effects of selection on linked sites. We here examine how the presence of direct purifying selection and background selection may bias demographic inference by evaluating two commonly-used methods (MSMC and fastsimcoal2), specifically studying how the underlying shape of the distribution of fitness effects (DFE) and the fraction of directly selected sites interact with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
94
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(104 citation statements)
references
References 97 publications
(115 reference statements)
8
94
1
1
Order By: Relevance
“…For example, a population bottleneck may lead to the accumulation of weakly deleterious mutations if drift overwhelms selection. As population size increases after a bottleneck, rapid purging of weakly deleterious mutations can occur, leading to deviations from the expectations of standard models of BGS, which assume constant population size (Torres et al 2020;Johri et al 2021). We have previously inferred a model of demographic history for M. m. castaneus, which suggested that population size has recently increased following a bottleneck (Booker and Keightley 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a population bottleneck may lead to the accumulation of weakly deleterious mutations if drift overwhelms selection. As population size increases after a bottleneck, rapid purging of weakly deleterious mutations can occur, leading to deviations from the expectations of standard models of BGS, which assume constant population size (Torres et al 2020;Johri et al 2021). We have previously inferred a model of demographic history for M. m. castaneus, which suggested that population size has recently increased following a bottleneck (Booker and Keightley 2018).…”
Section: Resultsmentioning
confidence: 99%
“…We performed an additional set of simulations incorporating this demographic history, but found that the relative reductions in diversity around both protein-coding exons and CNEs were very similar to those observed under constant population size (Figure S4). Note that the trajectory of the demographic history (bottleneck followed by recovery) we inferred may be an artefact of BGS (Ewing and Jensen 2016;Johri et al 2021). However, we proceeded with our analysis assuming estimates of B for a constant population size, because the variations in B around exons and CNEs were very similar with or without population size change.…”
Section: Resultsmentioning
confidence: 99%
“…According to population genetic theory, high coalescence rates are associated with low heterozygosity because heterozygosity is proportional to the coalescent time [ 73 ]. Although the authors attributed the high coalescence rates in South Africa to a low effective population size, they may also be a signal of selection and hitchhiking effects since the introduction of the aforementioned sex-ratio meiotic gene-drive system [ 74 , 75 ]. If so, then we predict low heterozygosity to be genome-region specific (i.e., near male-deleterious alleles) and not genome wide.…”
Section: Discussionmentioning
confidence: 99%
“…In order to account for these factors, more recent methods have been developed to jointly infer the demographic history simultaneously with the underlying DFE, without making assumptions about the selective effects of any particular class of sites. For example, the approximate Bayesian (ABC) approach recently proposed by Johri et al ( 2020 ) was shown to obtain accurate DFE inference using single time-point datasets, while uniquely accounting for the effects of background selection and the potential non-neutrality of synonymous sites (and see Johri et al 2021 ). Importantly, background selection expectations are themselves incorporated into the inference procedure; as such, the full DFE of newly arising mutations is estimated, even if, for example, the strongly deleterious mutations comprising the most deleterious class are not themselves sampled as polymorphic sites.…”
Section: Introductionmentioning
confidence: 99%